Can we improve the delivery of bedside teaching?. (October 2014) - Chapman, Renata; Wynter, Lucinda; Burgess, Annette; Mellis, Craig
Summary Background Bedside teaching is a vital component of clinical training in the medical curriculum. There is growing dissatisfaction among students regarding its delivery, and the main obstacles identified are: the availability of clinical tutors and access to suitable patients. Aim We sought to evaluate Sydney University medical students' perceptions and satisfaction with two structured bedside teaching methods. Methods We compared two strategies of bedside teaching. In the old, traditional method an experienced clinician was formally allocated to a group, and was 'responsible' for regular (usually weekly) bedside teaching for that group. In the new method a specified, protected clinical teaching time was chosen, during which time any tutor available (mainly Junior Medical Officers, JMOs) performed clinical bedside teaching for that student group. The strengths and weaknesses of the two methods were evaluated. Results A total of 104 students out of a possible 128 (81% participation rate) took part in this study. In the new method, 100 per cent of students had their scheduled bedside tutorial delivered every week, compared with 20 per cent in the old system, 70 per cent of tutors had patients prepared every week, compared with 25 per cent in the old system, and 64 per cent of students had 'no frustration' with clinical bedside tutorials, compared with 27 per cent in the old system. Conclusions The new method, using protected clinical teaching time at a specific scheduled weekly time, and using opportunistically available junior clinicians, is perceived by students as superior to the old method of one constant, experienced tutor allocated to a group. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> The main obstacles [to bedside teaching] are: the availability of clinical tutors and access to suitable patients </boxed-text>